Legal Analysis of the Settlement of the Criminal act of Theft with Aggregation Based on Legal Certainty (Case Study at Grobogan Resort Police) - Ardinal, Kevin; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Aggravated theft is one of the most common crimes in society and causes disruption to the sense of security, economic loss, and social stability. As the frontline of law enforcement, the police play a strategic role in handling these cases, including within the jurisdiction of the Grobogan Police. The purpose of this study is to determine and analyze the steps taken by the Grobogan Police in resolving aggravated theft, identify the obstacles encountered, and examine the solutions taken to overcome them. This research uses a juridical-sociological approach and descriptive-analytical specifications. Primary data were obtained through interviews with police officers at the Grobogan Police, while secondary data were sourced from laws and regulations (the Criminal Code, the Criminal Procedure Code, Law No. 2 of 2002 concerning the Police, and related regulations), legal literature, and other supporting documents. The analysis was conducted qualitatively by examining the synchronization between positive legal norms and their implementation practices in the field. The research results show that the Grobogan Police Department applies two main strategies in handling aggravated theft crimes: repressive (investigation, prosecution, arrest, and detention in accordance with the Criminal Procedure Code) and preventive (legal counseling, patrols in vulnerable areas, and coordination with the community). Obstacles faced include limited personnel and facilities, low public legal awareness, difficulties in providing evidence, and budget constraints. Efforts made to overcome these obstacles include improving coordination between law enforcement officers, intensifying patrols and legal counseling, and implementing non-litigation solutions through a restorative justice approach. The conclusion of this study is that the Grobogan Police's measures are in accordance with applicable legal provisions, but still face structural and cultural obstacles in their implementation. Therefore, strengthening the capacity of officers, increasing public legal awareness, and developing restorative justice mechanisms are essential so that the resolution of aggravated theft crimes can be more effective, just, and based on legal certainty.